Overseas Production and Exporting by the World's Largest Enterprises: A Study in Sourcing Policy - Buckley, Peter J.; Pearce, R. D. (Journal of International Business Studies, 1979)
The sourcing policy of a multinational enterprise is the result of the firm's decisions as to which of its production facilities shall service its various final markets. We can thus speak of an international network linking production to markets. Critical determinants of this policy are the firm's size, industry characteristics, and influences deriving from the firm's natioanality of ownership. We suggest that the research intensity is an important influence on sourcing policy, particularly through its effect on the firm's internal exports.